RECONSTRUCTING THE CONCEPT OF ISTIṬĀ’AH AL-NIKĀḤ: A MAQĀṢID AL-SHARĪ’AH RESPONSE TO FEMALE WAITHOOD - Saini Saini; Moh. Jeweherul Kalamiah Moh. Jeweherul Kalamiah; Mutia Tsamratus Sabrina Mutia Tsamratus Sabrina; Imam Bonjol Juhari Imam Bonjol Juhari; M. Syafiqil Umam M. Syafiqil Umam (Al-Majaalis : Jurnal Dirasat Islamiyah, 2026)
Marriage postponement (waithood) among educated Muslim women in Indonesia has increasingly challenged conventional understandings of marital readiness rooted in biological maturity and domestic competence. This study aims to examine how Muslim undergraduate women in Jember reconstruct the concept of Istiṭā’ah al-nikāḥ within the socio-religious pressures of Pandalungan culture and pesantren traditions. Existing studies largely interpret Istiṭā’ah through material and legal dimensions, while limited attention has been given to women’s reflective experiences in redefining marital readiness through intellectual and psychological capacities. This research employed a qualitative phenomenological approach using Interpretative Phenomenological Analysis (IPA). Data were collected through in-depth interviews and participant observation involving ten Muslim female undergraduate students aged 20–25 in Jember, and analysed using a contemporary Maqāṣid al-sharī’ah framework. The findings revealed a process of deconstruction toward traditional standards of marriage based on chronological age and domestic readiness, followed by the reconstruction of Istiṭā’ah as holistic preparedness grounded in intellectual sovereignty, emotional maturity, and reflective responsibility. Waithood was interpreted as an ethical and preventive strategy (sadd al-dharī’ah) to safeguard the intellect (ḥifẓ al-‘aql) and self (ḥifẓ al-nafs) before entering the mīthāqan ghalīẓā. This study demonstrates that modernity within the Pandalungan-pesantren context generates a reflective negotiation between religious commitment, women’s autonomy, and substantive marital readiness.